Development of Army’s Personnel Rights Filtering Tool - Chumdangpakdekul, Tissanarin; Kanjanapongporn, Attapol; Jeerasitkul, Udomsit (Journal of The Royal Thai Army Nurses, 2021)
This research designed a combination of both quantitative research and qualitative research. The objective were (1) to study Army personnel action handbook, survey the opinions on the use of the manual by collecting relevant data and analyzing it to obtain guidance, important information on the development of the Army personnel rights filtering tool, (2) to develop the Army’s personnel rights filtering tool and (3) to analyze the results of opinions on the effectiveness of the Army’s personnel rights filtering tool. In this research, data was collected from relevant personnel, both as part of the quantitative and qualitative research in which the data was collected by 3 steps: The first step was to collect quantitative data by distributing questionnaires to assess the quality of the personnel rights action manual for 95 people which are all personnel officers. The second step was to collect the qualitative data from in-depth interviews with a sample group of personnel rights experts who selected five specific samples. And the third step was to collect quantitative data by distributing the Army’s personnel rights filtering tool efficiency assessment form to a population of 95 people which are all personnel officers. The content validity indexes of these tools were 0.88, 1.00 and 1.00. The Cronbach’s alpha coefficient of 0.83, 0.94 and 0.97 respectively. Data analyzed by using frequency, percentage, average score and standard deviation. The overall performance of the Army’s personnel rights filter was very good (µ = 4.39). When considered individually, it was found that the effectiveness of the Army personnel rights filtering tool in 4 areas: Functional Requirement Test was at very good level (µ = 4.53) , Functional Test was at very good level (µ = 4.51) , Usability Test was at very good level (µ = 4.41). Lastly, the Security Test was at a good level (µ = 4.13). Amry’s Personnel Rights Filtering Tool reduces the workload of the operator, able to meet the needs of the user and can be used for practical purposes.